Clinical manifestations of adult patients requiring influenza-associated hospitalization: A prospective multicenter cohort study in Japan via internet surveillance. Issue 3 (March 2021) - Ishida, Tadashi; Seki, Masafumi; Oishi, Kazunori; Tateda, Kazuhiro; Fujita, Jiro; Kadota, Jun-ichi; Kawana, Akihiko; Izumikawa, Koichi; Kikuchi, Toshiaki; Ohmagari, Norio; Yamada, Mitsuhiro; Maruyama, Takaya; et al.
Abstract: Introduction: Influenza remains a clinically heavy burden worldwide. The objective of this study was to clarify clinical manifestations of severely ill patients infected with influenza. Methods: The clinical data for patients who were severely ill with influenza, and required hospitalization were gathered and analyzed between November 2014 and August 2019 (5 influenza seasons) using an internet-surveillance system. Results: A total of 924 patients were enrolled and analyzed. The median age was 78 years (IQR, 67–84), and the patients in the 2015–2016 season were significantly younger than those in other seasons. Pneumonia was the most common disease indicated as a cause for hospitalization, followed by a poor general condition and exacerbation of underlying respiratory diseases. Antiviral drugs were administered in 97.0% of the patients with peramivir being the most-frequently use antiviral. In-hospital death was recorded for 44 patients (4.8%). Multivariate analysis indicated that nursing home resident (OR: 6.554) and obesity (OR: 24.343) were independent predictors of in-hospital mortality. Conclusions: Complications of influenza infection remain a heavy burden especially among the elderly. Continuous nationwide surveillance will be required to grasp the actual situation of influenza epidemics. (UMIN000015989).